The Loss of Mother Tongue Among Youth: A Threat to Culture and National Identity - Eyato, Rahmat Alamsyah; Nazwa, Manda Revalina; Jeniarti, Ni Ketut Arik; Eyato, Alfiah Salsalbila (Journal of Advance in Language, Literature, and Education, 2025)
The loss of mother tongue among youth has become a pressing issue worldwide, particularly in linguistically diverse nations. This phenomenon threatens not only the survival of native languages but also the preservation of cultural heritage and national identity. This article examines the causes and implications of mother tongue decline among young generations through a comprehensive literature review and theoretical analysis. Factors such as globalization, educational policies, urbanization, and negative language attitudes are identified as key drivers of this trend. The study highlights the profound cultural and social consequences of mother tongue loss, including cultural erosion and weakened national unity. Recommendations are provided to promote mother tongue preservation through education, community engagement, positive language attitudes, technology, and supportive language policies. Preserving mother tongues is essential for sustaining cultural diversity and strengthening national identity in an increasingly globalized world.